Social Inclusion of Jyapus in Newar Community - Pokharel, Ram Raj (Patan Pragya, 2020)
Jpapus, one of the caste groups of Newar caste hierarchy, has been living with nears in the lalitpur city. The major population of Jyapus is found in the selected roles of city i. e. Chhayabahal, Lukhusi, Tanani and Nakabahil. This study focused on the social inclusion ofJyapus from socio-cultural and economic dimensions. To collect primary data on social inclusion of Jyapus researcher has had selected 231 households and applied data collection tolls such as Interview schedule, non-participant observation and Key- informants ‘interview. By using such data collection toll's researchers had found that major population of the Jyapus prefers to live in nuclear family. This study reveals that, among 231respondents 45 respondents were unmarried so that they are excluded from the total universe. So our universe is limited in 186 respondents. Thus, in the survey, 116 of the Jyapu respondents did love marriage. In regard with the educational status of the Jyapus majority, 150 Jyapus of the sample population were educated. In the study area, most of the Jyapus left their traditional work as agriculture and most of the Jyapus are nowadays doing services in different offices like other high caste Newars. One hundred thirty households in the study area used both Nepali and Newari language. Most of the 99 Jyapus are the followers of Buddhist religion. They also follow life cycle ceremonies as par with the other Newara in the study area. 187 Janus were not facing untouchability practiced in the study area by the other Newars. Similarly, majority, 185, Jyapus were participating in a different organization, so they are not excluded in the study area. While celebrating machinendranath jatra they also celebrate together abd there is no any other ways and places for the celebration. This indicates that they are included. In addition, during the feast they also eattogether with other Newars.